Concordance between practitioner questionnaire responses and observed clinical treatment recommendations for treatment of dentin hypersensitivity: findings from the National Dental Practice-Based Research Network - Mark S. Litaker; Dorota T. Kopycka-Kedzierawski; D. Brad Rindal; Jeffrey L. Fellows; Marc W. Heft; Cyril Meyerowitz; Sidney Chonowski; Gregg H. Gilbert; The National Dental PBRN Collaborative Group (BMC, 2019)
Abstract Background Few published reports have presented concordance between treatment choices selected by dentists in hypothetical clinical scenarios and treatment choices made by the same dentists in actual clinical practice. The aim of the current cross-sectional study, conducted within the Management of Dental Hypersensitivity (MDH) study, was to assess the potential value of practitioners' questionnaire responses regarding their typical treatment provided for management of dentin hypersensitivity (DH), by evaluating agreement between these responses and subsequently-observed recommendations recorded during actual clinical examinations. Methods A total of 171 practitioners enrolled in the National Dental Practice-Based Research Network completed both a questionnaire and a clinical study regarding methods they use to treat dental hypersensitivity. The questionnaire solicited first-, second- and third-choice products when prescribing or recommending management of dentin hypersensitivity. Agreement was calculated for first-choice products/recommendations and for inclusion in the top three choices, as identified by the practitioners, from 11 listed treatment options. Overall percent agreement and Cohen's kappa statistic were calculated, with associated 95% confidence intervals (CI). Associations between practitioner characteristics and agreement were also evaluated. Results For individual treatment modalities, percentage agreement ranged from 63 to 99%, depending on the specific item. Percentage agreement between typical treatment and actual treatment for each practitioner's top three treatment modalities, as a combined grouping, ranged from 61 to 100%. When these same agreement pairings were quantified to account for agreement above that expected by chance, kappa values were poor to low. Conclusions Concordance between hypothetical clinical scenarios and treatment choices made by the same dentists in actual clinical practice showed moderate to high levels of percentage agreement, but Cohen's kappa values suggested relatively low levels of agreement beyond that expected by chance. This analysis adds to the larger work of the network which has now observed a wide range of agreement between hypothetical and actual care, depending upon the specific diagnosis or treatment under consideration. Questionnaire data for DH might serve as a useful adjunct to clinical data regarding treatment recommendations, but agreement was not sufficiently high to justify use of questionnaires alone to characterize patterns of treatment for this particular condition.